Synthesis and crystal growth of Mg2Si by the liquid encapsulated vertical gradient freezing method. (24th July 2015) - Nakagawa, Reo; Katsumata, Hiroshi; Hashimoto, Satoshi; Sakuragi, Shiro
Abstract: The synthesis of Mg2 Si bulk crystals was performed by the vertical gradient freezing method using a KCl–MgCl2 eutectic liquid encapsulant. Stoichiometric polycrystalline Mg2 Si bulk crystals were successfully grown by changing the composition ratio of starting Mg and Si powders (Mg/Si) from 2.0 to 3.5. A chemical reaction between Mg2 Si and the crucible materials was inhibited using encapsulant materials, and the contamination by K or Cl originating from the encapsulant materials was not detected in almost all the samples. However, Mg evaporation could not be prevented completely during the synthesis and crystal growth. The optical band-gap energy of Mg2 Si bulk crystals became minimal (0.79 eV) at a Mg/Si ratio of 2.5, at which the maximum electron mobility of 202 cm 2 ·V −1 ·s −1 was obtained. These results indicate that the composition ratio of Mg/Si = 2.5 for starting Mg and Si powders was optimal for synthesizing Mg2 Si bulk crystals with high crystalline quality.